Public Financial Information Disclosure by the Regional Financial and Asset Management Agency (Case Study: Regional Financial and Asset Management Agency of Pekanbaru City) - Fajarwaty Kusumawardhani; Anisa Febrianti Putri; Alexsander Yandra (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study aims to identify and analyze Public Financial Information Disclosure by the Pekanbaru City Financial and Asset Management Agency whose information is incomplete on the official website. The research method used is qualitative with a phenomenological approach and the instruments used are observation, interviews, website tracking, and documentation. The indicators in this study are a combination of several theories, that is theory of democracy, good governance, and information disclosure, which finally obtained research indicators, that is accountability, transparency, communication, resources, leadership, and accessibility. The results of this study, that the disclosure of public financial information conducted by the BPKAD of Pekanbaru City still not implemented properly and also still not informative, presentation of financial data with online media is still used as a side job by employees, which eventually upload documents to be late or past the fiscal year. The problem is the number of employees who are minimal and less competent in their field also affects the implementation of public financial information disclosure by the BPKAD of Pekanbaru City.